The low-density lipoprotein receptor: Emerging post-transcriptional regulatory mechanisms - Ndoj, Klevis; Meurs, Amber; Papaioannou, Dimitra; Bjune, Katrine; Zelcer, Noam (Atherosclerosis, 2025)
Cholesterol is a vital component of cellular membranes and is an essential molecule in mammalian physiology. Yet dysregulation of hepatic cholesterol metabolism and an increase in plasma cholesterol is linked to development of atherosclerotic cardiovascular disease. Maintaining tight regulation of cholesterol homeostasis is therefore essential, elegantly highlighted by the control of hepatic low-density lipoprotein receptor (LDLR) abundance and associated lipoprotein clearance. The LDLR was discovered in the 1970's in the seminal work of Brown and Goldstein. This was followed by the development of statins, which promote hepatic clearance of LDL via the LDLR pathway. The discovery two decades ago of Proprotein Convertase Subtilisin–Kexin Type 9 (PCSK9), a secreted protein that binds to the LDLR ectodomain and promotes its degradation, and the clinical development of PCSK9 inhibitors has ushered an effort to uncover additional mechanisms that govern the function and abundance of the LDLR. In recent years this has led to the identification of novel post-transcriptional and post-translational mechanisms that govern the LDLR. This review focuses on these emerging regulatory mechanisms and specifically discusses: (1) Regulation of the LDLR mRNA by RNA-binding proteins and microRNAs, (2) Ubiquitin-dependent degradation of the LDLR protein by the E3 ubiquitin ligases inducible degrader of the LDLR (IDOL) and GOLIATH (RNF130), (3) Control of the LDLR pathway by the asialoglycoprotein receptor 1 (ASGR1), and (4) The role of LDLR ectodomain shedding mediated by membrane-type 1 matrix metalloprotease (MT1-MMP), Bone morphogenetic protein 1 (BMP1), and γ-secretase. Understanding the contribution of these emerging mechanisms to regulation of the LDLR is important for the development of novel LDLR-focused lipid-lowering strategies. [Display omitted] •Hepatic LDLR abundance is a central determinant of lipoprotein clearance.•Dysregulation of the LDLR pathway is associated with hypercholesterolemia and development of atherosclerosis.•Emerging post-transcriptional mechanisms that govern LDLR abundance offer potential new lipid-lowering strategies.